Productization of carbon handprint – A product management perspective - Pukar Jung Kunwar; Janne Harkonen; Harri Haapasalo; Iqra Sadaf Khan; Jukka Majava (Cleaner Engineering and Technology)
Despite its potential benefits, knowledge of the carbon handprint notion lacks the necessary means to address products and services in a structured manner, hindering appropriate methodological implementation and limiting support for firms' cleantech activities. Furthermore, an essential link to the product management perspective is lacking. To address this gap, this study details the components and features of products and their environmental impact to facilitate carbon handprint quantification and communication through productization. A conceptual research approach was adopted to develop a framework that links the carbon handprint to a broader product management perspective through productization. Selected theories provide a level of rationale for the productization of carbon handprints. This study presents illustrative examples involving motor vehicles and building construction and a generic approach to demonstrate how carbon handprints can be integrated into product structures over the engineering lifecycle. The productization approach enables businesses to effectively connect emissions and positive impacts on products. By broadening the understanding of carbon handprints through productization, companies can systematically utilize carbon emission information both internally and externally. This supports the overall product management perspective and enables effective analytics and reporting of carbon footprints and handprints.